2012
DOI: 10.1109/tsp.2011.2177834
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Uniformly Sampled Sequence From Nonuniformly Sampled Transient Sequence Using Symmetric Extension

Abstract: 24] D. M. Kodek and M. Krisper, "Telescopic rounding for suboptimal finite wordlength FIR digital filter design," Digit.Abstract-In this correspondence, reconstruction of a uniformly sampled sequence from a nonuniformly sampled transient sequence using symmetric extension is described. First, a relationship between the discrete Fourier transform (DFT) of a uniformly sampled sequence and the DFT of a nonuniformly sampled sequence is obtained. From the relationship, the formula to reconstruct the DFT of a unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Finally, we can reconstruct the uniformly sampled sequence by taking the inverse transform of the obtained DFRFT F α [m]. It is easy to show that the result of (16) reduces to the result of [23] in the Fourier domain when α = π/2.…”
Section: Relationship Between Uniform Samples and Non-uniform Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we can reconstruct the uniformly sampled sequence by taking the inverse transform of the obtained DFRFT F α [m]. It is easy to show that the result of (16) reduces to the result of [23] in the Fourier domain when α = π/2.…”
Section: Relationship Between Uniform Samples and Non-uniform Samplesmentioning
confidence: 99%
“…In(23), f [n] is the ideal uniformly sampled sequence, andf [n] is the reconstructed uniformly sampled sequence by taking the inverse transform of F…”
mentioning
confidence: 99%
“…Figure 6 demonstrates the relation between and * , and it is observed that the deviation * converges to 0.2942 when decreases to 0. In the following, our proposed method is compared with traditional methods, including CRT, Staggered PRF, and nonuniform sample [18], and the comparison results are presented in Table 2. Seen from Table 2, our proposed method transmits the least transmitting pulses.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…These sampling theorems establish the fact that a bandlimited or timelimited signal in the LCT domain can be completely reconstructed by a set of equidistantly spaced signal samples [26][27][28][29][30][31][32][33][34][35][36][37][38]. However, there are a variety of applications in which the data are sampled in other ways, such as non-uniformly in time or through multichannel data acquisition [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Examples in which non-uniform sampling may arise include data loss because of channel erasures and additive noise [39,41,49].…”
Section: Introductionmentioning
confidence: 99%
“…There are also applications where we can benefit from deliberately introducing more elaborate sampling schemes. Potential applications include flexible A/D converters, the orthogonal frequency division multiplexing system, data compression and image super-resolution [10,11,43,[54][55][56][57][58][59][60][61]. Therefore it is theoretically interesting and practically useful to consider the multichannel sampling expansion in the LCT domain.…”
Section: Introductionmentioning
confidence: 99%